2021
DOI: 10.1098/rspb.2021.0677
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive shifts underlie the divergence in wing morphology in bombycoid moths

Abstract: The evolution of flapping flight is linked to the prolific success of insects. Across Insecta, wing morphology diversified, strongly impacting aerodynamic performance. In the presence of ecological opportunity, discrete adaptive shifts and early bursts are two processes hypothesized to give rise to exceptional morphological diversification. Here, we use the sister-families Sphingidae and Saturniidae to answer how the evolution of aerodynamically important traits is linked to clade divergence and through what p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…For example, robotic flapping-wing micro air vehicles (FW-MAVs) have greater power efficiency and control than fixed-wing and rotary-wing aircraft of similar size [4,5]. Since the origin of flapping flight in insects, a wide diversity of wing morphologies (size, shape and mechanics), movements and flight behaviours have evolved [6][7][8][9]. A central question in the evolution of flapping flight is whether divergent strategies (combinations of wing shape, size and kinematics) arise to achieve similar flight performance.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, robotic flapping-wing micro air vehicles (FW-MAVs) have greater power efficiency and control than fixed-wing and rotary-wing aircraft of similar size [4,5]. Since the origin of flapping flight in insects, a wide diversity of wing morphologies (size, shape and mechanics), movements and flight behaviours have evolved [6][7][8][9]. A central question in the evolution of flapping flight is whether divergent strategies (combinations of wing shape, size and kinematics) arise to achieve similar flight performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hawkmoths (Sphingidae) and wild silk moths (Saturniidae) are diverse sister clades separated by approximately 60 Ma of evolution [9,16,17]. We recently showed that wing shape and size diverges between the families through an adaptive shift [9] coincident with the inter-familial divergence in life history [18][19][20] and flight behaviour [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations